'Metaprevotella massiliensis' gen. nov., sp. nov., isolated from human ileum. (May 2017) - Ricaboni, D.; Mailhe, M.; Cadoret, F.; Benezech, A.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of 'Metaprevotella massiliensis' strain Marseille-P-3114 T (CSURP3114) that was isolated from a human ileum sample.